1991
DOI: 10.1161/01.cir.83.3.902
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficiency of troponin T measurements in acute myocardial infarction.

Abstract: Thus, the data of the study indicate that the newly developed troponin T test improves the efficiency of serodiagnostic tools for the detection of myocardial cell necrosis as compared with conventionally used cardiac enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
314
2
24

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 733 publications
(348 citation statements)
references
References 30 publications
8
314
2
24
Order By: Relevance
“…In fact, serum concentrations of troponin I and T, also belonging to the EF-hand protein family, are currently used as sensitive indicators of cardiac injury (38). For S100A1 a correlation between the extent of myocardial damage and the S100A1 serum concentration has also been reported (11).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, serum concentrations of troponin I and T, also belonging to the EF-hand protein family, are currently used as sensitive indicators of cardiac injury (38). For S100A1 a correlation between the extent of myocardial damage and the S100A1 serum concentration has also been reported (11).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 7 emphasized that cTnT elevations are seen at a minimum 3--4 h after the onset of symptoms. Other studies, however, reported an elevated cTnT on admission within 2 h after symptom onset.…”
Section: Predictors Of Admission Ctntmentioning
confidence: 97%
“…As expression of cardiac troponin T (cTnT) or troponin I (cTnI) exclusively takes place in cardiomyocytes, elevated levels indicate myocardial injury [11]. Due to biphasic release kinetics, an early peak within 24 h is observed due to release of a cytoplasmic pool and a plateau after 48-72 h is observed due to proteolytic degradation of the contraction apparatus [12,13].…”
Section: Cardiac Troponin: Preferred and Gold Standard Biomarkermentioning
confidence: 99%